A Case of Recurrent Stroke in Left MCA Stenosis - Bhuiyan, AA; Shahriar, SMH; Nahid, F; Alam, MJ (Pulse, 2014)
We report the clinical, neuro-radiological findings of a young man who was admitted to Apollo Hospitals Dhaka, Bangladesh because of abrupt onset of aphasia and right sided mild hemiparesis. He had two strokes six days apart one and half years ago. His past medical history was significant for HTN, smoking. His MRI of the Brain showed acute infarct in left middle cerebral artery (MCA) region congruent with his symptoms and signs. MRA done during his first stroke showed left MCA long segment luminal narrowing. DSA done during initial stroke showed complete occlusion of superior division of left MCA with collateral flow from left anterior cerebral artery (ACA) and posterior cerebral artery (PCA) to left MCA. Other extensive work up for stroke etiology was inconclusive. His stroke recurrence points towards left MCA stenosis (which is reversible) with good collateral circulation which helped the patient get significant neurological recovery. In young patients with recurrent strokes with or without conventional risk factors, vascular anomalies (intra-cranial and extra-cranial) should be investigated to find out the other rare causes for strokes. As TEE was not done here, it conclusively can not be ascertained that some cardio-embolic source of stroke was not present. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20359 Pulse Vol.6 January-December 2013 p.70-74